Syarikat Janazata / Muhamed Sukry Sejeli ... [et. al] - Sejel, Muhamed Sukry; Pirmang, Luqman; Sandek, Jumaniza; Basran, Rahmat Hidayat (2011)
The marketing concept rest on the philosophy that all marketing activities must satisfy customer need and wants and also creates need with fulfil the demands in the markets. A marketing plan is written document that details the necessary action to achieve one or more markeing objectives. It can be for a procuct or service, a brand, or a product line. Marketing plan coverage is between one to three years. A marketing plan may be part of an overall business plan. Solid marketing strategy is the foundation of a well-written marketing plan. While a marketing plan contains a list of actions, a marketing plan without a sound strategic foundation is of little use.